Urban Changes in the Traditional Residential Neighborhood Case: The Bab El-Louz neighborhood in Bejaia - Bounouni, Sofiane (Technium Social Sciences Journal, 2023)
Bejaia, as many Algerian cities, has undergone profound economic, social, political and urbanistic changes, but is today in a state of anarchy in total abstraction with the urban architectural heritage. In the heart of its center, the district of Bab El-Louz is considered as one of the oldest and most important districts of the city of Bejaia due to its strategic position, the residential character par excellence and its traditional architecture. In recent years, the neighborhood of Bab El-Louz is subject to remarkable changes in its residential space, changes that are made in an informal and unplanned manner, based on individual initiatives to meet the needs of the current situation. These transformations are becoming more and more significant from one day to the next, which has led to a real mutation of the Bab Elouz district, which is spatial, social and functional and which needs to be studied and analyzed. The purpose of this research is to show the consequences of mutation on the basis of architectural and urban transformations and mutations of the residential space of the Bab El-Louz district which threaten the survival of a historical heritage and the future of this district.